Integrating Climate Products in the Existing Undergraduate Curricula: An Approach to Respond to Climate Change through Climate Education - Belay, Berhanu; Ambaw, Gebermedihin; Amha, Yosef; Workneh, Sintayehu; Terefe, Tadesse; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate change is real, and the severity of the problem is critical in developing countries where agriculture is the backbone of the economy. The agricultural sector in Ethiopia is highly climate dependent. More than 95% of farmed land grows crops under rain-fed agriculture. Given continually increasing climate change trends and variability, Ethiopia is expected to get hotter in the foreseeable future. This situation will increase small farm households' vulnerability to climate-related shocks that may induce food insecurity, malnutrition, diet-related non-communicable diseases, and large-scale displacements. Since there is no vaccine for climate change, equipping next-generation agricultural science graduates with the concepts of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) is one of the best ways to address climate change related challenges and envision knowledge-based innovative practices that strengthen adaptation to climate change and leverage mitigation actions. Climate Change Education (CCE) and trainings have long been recognized by the national CCE strategy (2017-2030), the United Nations Framework Convention on Climate Change, the Paris Climate Change Agreement, and the Sustainable Development Goals of the United Nations (Agenda 2030) as key tools to unravel the complex and multi-sectorial challenges induced/posed by climate change. Thus, Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA), in collaboration with Ethiopian Higher Education, initiated the integration of the concept of CIS and CSA in the agricultural program in Ethiopia. Demand was created among Ethiopian public universities by engaging university vice presidents, Professionals from agriculture and climate sciences. Through consultation workshops and discussions with university management, it was noted that integrating climate products as a sub-chapter and case studies in the existing curriculum is one of the strategies to respond to climate change through education. To implement the integration of climate products (CIS, CSA, CRMA and CB) in the existing curricula, a committee was named to collect the agriculture curricula, execute gap analyses and recommend the integration of CP in the existing curriculum. A draft document was produced and circulated among committees, and the comments were received. The gap analyses revealed that there were 11 climate-related courses offered in 10 departments in the Undergraduate program. The courses were either shallowly addressed or do not address climate products in the curricula. This has necessitated integrating the existing curriculum with climate products to contribute to the efforts of climate education, ensuring the relevance and quality of education. A validation workshop was organized, and the findings of the gap analyses and gap-filling recommendations were presented to university representatives drawn from 27 Universities. Comments in the validation workshop were included, and a final integrated curriculum was approved. A document that integrated climate products were produced and passed to the universities, and action points and a timeline was established for implementation. It was recommended that incorporating CP in the curricula be extended to other disciplines (e.g., health, Water Engineering etc.). It was also suggested to extend the experience to PG programs of all disciplines coupled with strong capacity-building efforts for teaching staff. It was also recommended that a standalone, common course and credited courses should be offered to all University students to advance climate education and respond to climate change.